Savoring moderates the association between cancer‐specific physical symptoms and depressive symptoms. Issue 2 (16th March 2016) - Hou, Wai Kai; Lau, Kam Man; Ng, Sin Man; Cheng, Ashley Chi Kin; Shum, Tracy Chui Yu; Cheng, Sheung‐tak; Cheung, Hester Yui Shan
Abstract: Background: This study investigated the associations of savoring with cancer‐specific physical symptoms, psychological distress, and psychological well‐being and the moderating effect of savoring in the associations between physical symptoms and psychological outcomes among cancer patients. Methods: A total of 263 Chinese adults recently diagnosed with cancer (mean time since diagnosis = 43.72 days, SD = 38.20) were recruited and administered a questionnaire assessing cancer‐specific physical symptoms, perceived capability of savoring the moment, psychological distress, and psychological well‐being within six months following diagnosis. Results: Structural equation modeling revealed significant associations of savoring with physical symptoms and psychological distress and well‐being ( β = −0.41–0.54, p < 0.0001). Savoring significantly moderated the association between physical symptoms and depressive symptoms. Simple slope tests revealed that the association was not significant at higher levels of savoring (estimate = 0.15, z = 0.49, p = 0.62) whereas it was stronger at lower (estimate = 1.11, z = 4.81, p < 0.001) and medium (estimate = 0.63, z = 3.04, p < 0.01) levels of savoring. The effects of demographic and medical covariates were controlled for in all models. Conclusions: The findings suggest that savoring is positively associated with physical and psychological functioning among people with cancer. The link between physical symptoms and depressive symptoms could be exacerbated at lower levels of savoring. Fostering savoring beliefs and practices could be a significant psychological component of symptom management among cancer patients. Copyright © 2016 John Wiley & Sons, Ltd.